A Ccritical Rreview of the Bbook of “Ccapitalism, Ffamily and Ppersonal Llife” - Maryam Eskafi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this paper is to critically evaluate the book "Capitalism, Family and Personal Life." The author's question is how capitalism and feminism differentiate between two public and private spheres in the family. The researcher has come up with a part of the criticism by matching the translated text with the original text and looking at the sources of the subject. Then, by examining the text of the interpreter, she criticized the other part. But in general, the critical thinking method has been used to evaluate the book. The researcher's evaluation showed that, despite the complexity of the original text, the interpreter has provided a thorough and psychological translation of the book; nevertheless, given the fact that it was translated and published in Iran, it would have been better for the translator to include some differences  in the footnotes about the West, the Iranian community, and Eastern societies. Despite the historical importance of the present book, given the content problems, methodological problems, facial problems and its very incomplete translation from the original text in Persian, it does not seem to suggest that a suitable source, as a textbook, be offered to students. If this book is supposed to be introduced at university, it needs major reforms.